Physical training at sub-threshold intensity reduces the prevalence of hepatic steatosis after high-fat diet in rats - Valdemar Guedes da Silva; Fabrício Cesar de Paula Ravagnani; Allan da Mata Godois; Odashiro Maçanori; Fabrício Azevedo Voltarelli; Celso Massaschi Inouye; Christianne de Faria Coelho-Ravagnani (Universidade Estadual Paulista (UNESP), 2015)
The purpose of the present study was to evaluate the effects of swimming physical training with sub-threshold load on the prevalence of hepatic steatosis in Wistar rats fed high-fat diets (cafeteria or baru). After 2 months of cafeteria diet administration, the rats were separated into 6 groups: Sedentary or Trained Baru diet; Sedentary or Trained Cafeteria diet; Sedentary or Trained standard diet. The trained groups were subjected to swimming exercise at sub-threshold intensity (2% of body weight) during 8 weeks, 5x/week, 1h/day. The body weight and hepatohistological changes were analyzed. Sedentary groups fed high-fat diets presented higher body weight gain when compared to control trained group. The swimming training at the proposed intensity was able to prevent the hepatic steatosis in rats fed high-fat diets.